Visual Media in Teaching English Vocabulary - Wattimena, Berthy D. (Huele: Journal of Applied Linguistics, Literature and Culture, 2022)
This library research examines the implementation and effectiveness of visual media in teaching English vocabulary to young learners in EFL contexts. Through analysis of theoretical frameworks and empirical studies, this research investigates how various forms of visual media facilitate vocabulary acquisition and retention in language learning environments. The study employed library research methodology to analyze documents related to visual media usage in EFL contexts, teaching methodologies, and vocabulary acquisition strategies. The analysis focused on three key aspects: the nature of media use, the concept of media implementation, and effective application methods in EFL contexts. The findings reveal that visual media serves as an effective pedagogical tool, significantly enhancing student engagement, motivation, and vocabulary retention. Different types of visual media, including pictures, cartoons, posters, and digital presentations, offer unique advantages in vocabulary instruction, with their effectiveness varying based on learner characteristics and instructional contexts. This research contributes to the understanding of media-enhanced language learning and provides practical implications for EFL teachers. Furthermore, the study emphasizes the importance of appropriate media selection and implementation strategies in vocabulary instruction, particularly for young learners in EFL settings. The findings suggest that systematic integration of visual media in vocabulary instruction can lead to improved learning outcomes and more engaging educational experiences.